2019
DOI: 10.2196/cancer.7850
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Using Twitter to Recruit Cancer Survivors and Their Willingness to Participate in Nutrition Research and Web-Based Interventions: A Cross-Sectional Study

Abstract: BackgroundSocial media is rapidly changing how cancer survivors search for and share health information and can potentially serve as a cost-effective channel to reach cancer survivors and invite them to participate in nutrition intervention programs.ObjectiveThis study aimed to assess the feasibility of using Twitter to recruit cancer survivors for a web-based survey and assess their willingness to complete web-based nutrition surveys, donate biospecimens, and to be contacted about web-based nutrition programs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
3
17
2
Order By: Relevance
“…An audit of the reach of our study advertisements demonstrates that in both the cases, Twitter and Facebook are inefficient sources of identifying cancer survivors: as reported elsewhere too [57,58], there was very low pull-through recruitment rate from the total population reached, despite high (and increasing) population-level prevalence of cancer. It is interesting that our Twitter recruitment was so much poorer than that reported by Keaver et al [28]; however, there are two important differences between that publication and our own work. First, our work recruited directly into a comparatively high-burden research study rather than exploring (in a cross-sectional survey) willingness to participate in future studies.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…An audit of the reach of our study advertisements demonstrates that in both the cases, Twitter and Facebook are inefficient sources of identifying cancer survivors: as reported elsewhere too [57,58], there was very low pull-through recruitment rate from the total population reached, despite high (and increasing) population-level prevalence of cancer. It is interesting that our Twitter recruitment was so much poorer than that reported by Keaver et al [28]; however, there are two important differences between that publication and our own work. First, our work recruited directly into a comparatively high-burden research study rather than exploring (in a cross-sectional survey) willingness to participate in future studies.…”
Section: Discussioncontrasting
confidence: 68%
“…There may well be a case to be made for a recruitment strategy with mixed traditional and online recruitment until generational issues in social media usage become less pronounced. Based on the study by Keaver et al [28], we were also not able to demonstrate that online recruitment can overcome the gender bias of participants in cancer survivorship research; this is a considerable problem for our field and there are clearly other reasons why men do not participate in our research than need to be further explored. We were interested to see that we recruited a larger sub-sample of participants who identified as non-heterosexual than in other survivorship research [44,59]; we suspect that the anonymity of our recruitment and data collection methods may have led to a higher rate of disclosure of non-heterosexuality.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…compared a sample recruited via Twitter with a nationally representative sample of 1550 cancer survivors in NHANES (National Health and Nutrition Examination Survey) and similarly found that respondents to social media posts were younger and more likely to be female, non-Hispanic White, to have a higher education and to be within five years of their initial diagnosis. 23 This may be due to the makeup of users on social media platforms, user activity or platform algorithms that determine exposure to study-relevant posts, effectiveness (or lack thereof) of targeted marketing to reach different groups, or differences in response rates across groups. Conversely, registry-based sampling and recruitment through cancer centers and clinics have been shown to be biased toward patients with private health insurance or Medicare and those who are in active or recent treatment and engaged with clinical care teams, with differences in ‘opt-out’ rates across demographic subgroups reported.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes some of the latest publications regarding social networks as health problems or interventions. This research focused on the latest publications in major journals in the health field, such as the Journal of Medical Internet Research [25]. In this sense, the results showed that the health and education area tend to focus on the positive outcomes of using social networks.…”
Section: Introductionmentioning
confidence: 99%